TITIK TEMU PENDAPAT SUNNI DAN SYIAH TENTANG NIKAH MUT’AH - Muhammad Amanudin; Jumni Nelli (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This paper describes the debate about mut'ah marriage between Shia and Sunni. The debate between the two Sunni and Shi'a groups regarding mut'ah marriage has both strong arguments and arguments. But what is interesting is when the groups that allow and do not allow mut'ah marriages use the same opinion with the same figure, namely Ibn Abbas and Sayyidina  Ali. The meeting point between the Shia and Sunni groups in mut'ah marriage is a legal act that must be positioned and placed in a moderate and legal portion, the permissibility of carrying out a mut'ah marriage must be considered as an emergency law, not something that is generally permitted.